Thinking About Religious Texts Anthropologically - Kahn, Joel S. (Heritage of Nusantara: International Journal of Religious Literature and Heritage, 2015)
This  paper  addresses  the  conference  themes  by  asking  what  contribution anthropology  can  make  to  the  study  of  religious  literature  and  heritage.  In particular I will discuss ways in which anthropologists engage with religious texts. The paper begins with an assessment of what is probably the dominant approach  to  religious  texts  in  mainstream  anthropology  and  sociology, namely  avoiding  them  and  focussing  instead  on  the  religious  ‘practices’  of ‘ordinary believers’. Arguing that this tendency to neglect the study of texts is  ill-advised,  the  paper  looks  at  the  reasons  why  anthropologists  need  to engage  with  contemporary  religious  texts,  particularly  in  their  studies of/in the  modern  Muslim  world.  Drawing  on  the  insights  of  anthropologist  of religion  Joel  Robbins  into  what  he  called  the  “awkward  relationship” between anthropology and theology, the paper proposes three possible ways in  which  anthropology  might  engage  with  religious  literature.  Based  on  a reading  of  three  rather  different  modern  texts  on  or  about  Islam,  thestrengths  and  weaknesses  of  each  of  the  three  modes  of  anthropological engagement is assessed and a case is made for Robbins’s third approach on the  grounds  that  it  offers  a  way  out  of  the  impasse  in  which  mainstream anthropology  of  religion  finds  itself,  caught  as  it  is  between  the  ‘emic’  and the ‘etic’, i.e. between ontologically different worlds.